Study on external cavity diode laser with a wide mode-hopping free tuning range - Zhang, Aiguo; Qiao, Shan; Sheng, Liwen; Huang, Lin; Liu, Zhiming; Ju, Junwei; Zhang, Zhihui; Yin, Bingqi; Li, Peng; Liu, Jiaqing; Wei, Yu (Frontiers in Physics, 2022)
A wide mode-hopping free and narrow linewidth tunable laser diode source with a Littman-Metcalf arrangement based on a diffraction grating is presented. Several experiments are carried out to demonstrate the tuning characteristics and spectral linewidth of the proposed external-cavity diode laser source. A wide no mode-hopping continuous wavelength tuning range about 59.13nm in ultra-C-band with a narrow spectral linewidth of less than 100kHz is obtained. An optical signal to noise ratio of more than 65dB and an output power more than 14.8dBm over the whole tuning range can also be realized in a long-term free running condition. The proposed tunable laser allows simultaneously mode-hopping free and narrow linewidth tunable radiation, thus opening a door for practical application such as coherent detection.